Strategic renewal with Tajdid approach on community vegetable garden - Mhd. Sarif, Suhaimi; Zainudin, Dolhadi (International Islamic University Malaysia, 2019)
This paper reports strategic renewal with tajdid approach in revitalising community vegetable garden. The need for renewal is to sustain the vegetable garden with balanced approach. The main objective of the vegetable garden is to provide a space for sustainable production and consumption practice. While the model is necessary, it provides a space for social interactions and civilizational.